AFR and fuel cut-off modeling of LPG-fueled engine based on engine, transmission, and brake system using fuzzy logic controller (FLC) - Setiyo, Muji; Munahar, Suroto (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2017)
During deceleration, continuous fuel flows into the engine not only causing over fuel consumption but also increasing exhausts emissions. Therefore, this paper presents a simulation of AFR and fuel cut-off modeling in the LPG-fueled vehicle using Fuzzy Logic Controller (FLC). The third generation of LPG kits (Liquid Phase Injection, LPI) was chosen due to its technological equivalency to EFI gasoline engine and promising to be developed. Given that the fuel system control is complex and non-linear, FLC has been selected because of simple, easy to understand, and tolerant to improper data. Simulation results show that the AFR and fuel cut-off controller able to maintenance AFR at the stoichiometric range during normal operation and able to cut the fuel flow at deceleration time for saving fuel and reducing emissions.